Culturally Sensitive Field Protocol: The Manomin Project ... - Luby, Brittany; Bradford, Andrea; Mehltretter, Samantha; Luby, Allan; Wagamese, Archie; Henry, Barry; Henry, Clarence; Strong, Danny; Henry, John; Klein, Josephine; Kabestra, Larry; Greene, Terry; et al. (Borealis, 2021)
This field protocol was developed to guide respectful, ethical and culturally sensitive research activities in the project, Intensifying manomin (Zizania palustris) growth in environments altered by colonial settlement in ways that are responsive to Anishinaabe knowledge and values. The Manomin Project, funded by George Weston Ltd., aims to integrate environmental data retrieved by University of Guelph (UofG) researchers with cultural and ecological knowledge from Niisaachewan Anishinaabe Nation with the objective of restoring Manomin (commonly known in English as “wild rice”) on the Upper Winnipeg River. At present, the Research Ethics Board at U of G does not recognize Manomin as a spirit being like the Anishinabeg do. Due to differences in cultural beliefs and ways of knowing, it was essential to the project that a culturally sensitive field protocol be developed to sustain a healthy and respectful relationship between U of G researchers, Niisaachewan Anishinaabe Nation (NAN), and Manomin (a non-human ...